Untargeted metabolomics profiling for the geographical authentication of traditional pempek using high-resolution orbitrap mass spectrometry - Agus Supriadi; Sherly Ridhowati; Daniel Saputra; Wulandari; Shanti Dwita Lestari (Food Chemistry Advances)
The geographical authentication of traditional foods, such as Pempek, is increasingly important due to globalisation and rising consumer demand for product authenticity. Pempek, a traditional Indonesian dish, varies by region due to differences in fish species and local preparation methods. This study utilised untargeted metabolomics with High-Resolution Orbitrap Mass Spectrometry (HRMS) to identify metabolite markers associated with the geographical origin of Pempek. Samples from Palembang, Jambi, and other regions were analysed using chemometric techniques, revealing significant variations in metabolic profiles between these areas. The HRMS-based approach successfully detected region-specific markers and demonstrated its potential as a reliable method for geographical authentication, fostering confidence for the future of food authenticity. These findings contribute to preserving the cultural and economic significance of traditional foods like Pempek and highlight the broader application of metabolomics in food authentication.